2022
DOI: 10.1021/acs.cgd.2c00264
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Implications of Extraordinarily Soft Crystals in a Fixed-Dose Combination Hepatitis C Regimen

Abstract: Paritaprevir and ombitasvir are part of a triple combination, first-generation, direct-acting antiviral regimen as a fixed-dose tablet. The commercially manufactured Form II of paritaprevir and Form I of ombitasvir are high stoichiometry crystalline hydrates with 2.5 and 4.5 molar equivalent of water, respectively. The dominant (001) surface for paritaprevir interacts with adjacent non-interlocking layers via weak dispersion forces due to large interlayer d-spacing. On the other hand, the dominant (001) surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…There are good relationships between an investigational pharmaceutical compound's crystal structure, crystal morphology, and physicochemical characteristics [23,24]. The theoretical crystal morphology of (1) was simulated using Materials Studio 7.0 [25] utilizing the Bravais-Friedel-Donnay-Harker (BFDH) model and growth morphology (GM) models.…”
Section: Growth Morphology Predictionmentioning
confidence: 99%
“…There are good relationships between an investigational pharmaceutical compound's crystal structure, crystal morphology, and physicochemical characteristics [23,24]. The theoretical crystal morphology of (1) was simulated using Materials Studio 7.0 [25] utilizing the Bravais-Friedel-Donnay-Harker (BFDH) model and growth morphology (GM) models.…”
Section: Growth Morphology Predictionmentioning
confidence: 99%
“…Polymorphism is related to the ability of a compound to crystallize in different crystallographic structures but with the same chemical composition. For organic materials, where the solid-state chemistry is mostly characterized by a combination of weak undirected van der Waals interactions coupled, in some cases, with stronger directed hydrogen bonds (HBs), polymorphism is not an unexpected phenomenon (e.g., ref ). Indeed, it has often been reported that the number of polymorphic forms discovered for a given material depends upon the efforts (time and resources) committed. ,, In conformational polymorphism, flexible organic molecules can adapt different molecular conformations, resulting in the different polymorphic forms. ,, As a result, a multitude of polymorphic forms may be observed e.g., in tolfenamic acid and paritaprevir, ritonavir, ROY, , acridine, and aripiprazole . For pharmaceutical materials, the different polymorphs of a substance may exhibit different physicochemical properties, such as solubility, stability, density, and bioavailability. ,, Therefore, gaining an understanding and then control of the crystallization of an active pharmaceutical ingredient (API) from solution can form an essential part of both its development and subsequent formulation as a drug product.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms could include the effects of solute/solvent interactions in the solution state on the nucleation process and hence on polymorphism. , Nucleation can play a significant role in controlling the final product properties , with its rate being very sensitive to solution chemistry. ,,, Using classical nucleation theory (CNT), the interfacial energies between the solid and solution forms can be calculated and correlated to solvent properties such as solubility, boiling point, and dipole moment to examine nucleation behavior. Although, nucleation from solution can be strongly influenced by solvent selection, the detailed mechanisms underpinning solvent-dependent behavior also remain quite elusive. In this respect, modeling intermolecular solute/solvent interactions provided helpful insights into both the strength of solvation interactions and the associated solvent coordination to solute molecules as a function of solvent type. ,, Crystallizability as a function of solvent selection has also been assessed through meta-stable zone width (MSZW) measurements , and also through the determination of nucleation kinetics using CNT. ,,,, …”
Section: Introductionmentioning
confidence: 99%